The tale of three trees : a traditional folktale - Hunt, Angela Elwell, 1957-; Jonke, Tim (Colorado Springs, CO : David C. Cook, 1989)
Three trees that dream of greatness are surprised by the way their dreams come true.
Original edition published in English under the title The Tale of Three Trees by Lion Hudson plc., Oxford, England.
Accelerated Reader AR
Keywords: Jesus Christ -- Folklore -- Juvenile literature; Folklore -- United States -- Juvenile literature; Trees -- Folklore